Constraints experienced by restaurateurs and caterers in Indonesia for halal certification - Prabowo, Sulistyo; Abd Rahman, Azmawani; Ab Rahman, Suhaimi; Abu Samah, Asnarulkhadi (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
World halal business as well as awareness in halal products and services consumption has been growing rapidly for the last few years. However, many industry players have not realized the huge potential of halal business. In food industry, service sectors like restaurants and caterings show less concern on halal certification than to that in the manufacturing sector. This study explores the constraint in the adoption of halal assurance system HAS 23000 as a prerequisite to halal certifications in food service industries in East Kalimantan (Kaltim), Indonesia. This study used an in-depth interview in qualitative data collection. Fifteen respondents representing eleven caterers and four restaurateurs were interviewed. An open ended question was employed to elicit the required data. The study identified some internal and external factors as the constraint in the adoption of halal certification. The result found that lack of human resources capability, as well as lack of socialization and information was the most used theme addressed by the participants. These factors led to the lack of knowledge and awareness.